The influence of leadership behavior, commitment, and employee motivation on employee performance: a study at pt. adiwraksa atyanta in sukoharjo - Fauzi, Rama Anwar; Kusdiyanto, Kusdiyanto (Jurnal Mantik, 2025)
This study investigates the impact of leadership behavior, commitment, and employee motivation on employee performance at PT. Adiwraksa Atyanta in Sukoharjo. Using a quantitative approach with a positivist philosophy, the research was conducted from July 2023 until the end of the study period, employing random sampling and data collection through interviews and questionnaires with a Likert scale. Data analysis was performed using PLS-SEM via SMARTPLS to evaluate both outer and inner models. Outer model evaluations included convergent validity, discriminant validity, and reliability, while the inner model assessed structural relationships. The results reveal that leadership behavior, commitment, and employee motivation all have a significant positive effect on work performance. However, the study faced limitations such as using a closed-ended questionnaire and focusing solely on the variables of leadership behavior, commitment, and motivation. It is recommended that future research incorporates a larger and more diverse sample and explores additional factors that may influence employee performance